Gambaran Pendidikan Anak yang Membutuhkan Perlindungan Khusus - Ajisuksmo, Clara R. P. (Makara Human Behavior Studies in Asia, 2009)
In order to recognize and to fulfill the children’s rights, as well as to protect them, the Indonesian Government ratified the Convention on the Rights of the Children (CRC) in 1990 and approved Law No. 23 on Child Protection in 2002. Article 28 of CRC states that the states parties recognize that the right of the children to have education, and to achieve this right progressively on the basis of equal opportunity. This statement implies that states parties shall make primary education compulsory, available and free to all. The states parties shall also encourage the development of different forms of secondary education. In fact, many children could not participate in and therefore should drop out from their basic education because their very poor parents. Instead, they have to work to support their family’s life. This survey was intended to give a descriptive overview of the educational status and level, as well as to offer forms of alternative education for children who are categorized as in needs of special protection (CNSP). In addition, this survey was intended to identify individuals or institutions that the poor children school tuition. This survey involved 165 children below 18 years of age who were assisted in by 7 (seven) NGOs in Jakarta, Bogor, and Surabaya which have a partnership with PLAN International.